2005
DOI: 10.1007/s10151-005-0207-4
|View full text |Cite
|
Sign up to set email alerts
|

Transanal rectocele repair using EndoGIA: short–term results of a prospective study

Abstract: Transanal rectocele repair with linear stapler applied in selected patients is safe and easy to perform. Short-term results are safisfactory. Complete investigations of impaired defecation and selection of patients are needed to achieve satisfactory results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…They first reported the good results of transanal rectocele repair with a linear stapler in French patients in 2004. Similar results have recently been demonstrated by two European studies [15,16]. In all three studies, the authors emphasized that the transanal approach using a linear stapler was an easy, safe, and useful procedure for the correction of symptomatic rectocele.…”
supporting
confidence: 71%
See 3 more Smart Citations
“…They first reported the good results of transanal rectocele repair with a linear stapler in French patients in 2004. Similar results have recently been demonstrated by two European studies [15,16]. In all three studies, the authors emphasized that the transanal approach using a linear stapler was an easy, safe, and useful procedure for the correction of symptomatic rectocele.…”
supporting
confidence: 71%
“…In recent years, three studies confirmed the effectiveness of the Bresler procedure in the treatment of ODS [14][15][16]. D'Avolio et al reported their results of the Bresler procedure in 15 patients with a follow-up of 3 months.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…If conservative management failed to relieve symptoms, surgical treatment was advocated. Endorectal rectocele repair has been performed by colorectal surgeons [3][4][5] . However, after endorectal repair difficult evacuation has been reported [6,7] .…”
Section: Introductionmentioning
confidence: 99%